Agents, assumptions and motivations behind REDD+ : creating an international forest regime - Lovera-Bilderbeek, Simone; Edward Elgar Publishing (Edward Elgar Pub., 2019)
It was hoped that by paying forest dependent peoples and countries for their "service" of conserving their forests, REDD+ would lead to a reduction in deforestation greenhouse gases. The complexities have, however, left some ambiguities. It was never agreed who would pay for the program, and it has been criticized as ignoring the root causes of forest loss. Considering the motivations of those who promoted REDD+ this book proposes remedies to its shortfalls and recommends more efficient, equitable and effective conservation policies. Describing REDD+ from an agency perspective, this book provides a first-hand account of how individuals and institutions influenced international negotiations. It offers a comparative analysis of REDD+ as a forest conservation regime and of the way it was incorporated into the 2015 Paris Agreement. In doing so, this book shows how contextual inequalities and power imbalances can result in international regimes which favor the economically powerful, and proposes providing greater roles for the assumed beneficiaries of environmental agreements in negotiations. This is an excellent introduction to REDD+, its background and execution, and will be a vital resource for students of international environmental governance, as well as for academics and researchers working on REDD+, forest policy and international governance in general.
Contents: Acknowledgments -- 1. Introduction: The role of agents and the establishment of the REDD+ Regime -- 2. The role of agents in earth system governance -- 3. The agency of governments in REDD+ -- 4. The agency of non-state actors in REDD+ -- 5. The assumptions behind REDD+ -- 6. The effectiveness of the REDD+ Regime -- 7. The economic efficiency of the REDD+ Regime -- 8. The social equity of the REDD+ Regime -- 9. Conclusions -- Bibliography -- Summary -- Index.
Includes bibliographical references and index.
Description based on print record.
Keywords: Forest degradation -- Control; Forestry law and legislation; Reducing Emissions from Deforestation and Forest Degradation (Program); Electronic books